2021
DOI: 10.3847/1538-4357/abf246
|View full text |Cite
|
Sign up to set email alerts
|

AGNs on the Move: A Search for Off-nuclear AGNs from Recoiling Supermassive Black Holes and Ongoing Galaxy Mergers with the Zwicky Transient Facility

Abstract: A supermassive black hole (SMBH) ejected from the potential well of its host galaxy via gravitational wave recoil carries important information about the mass ratio and spin alignment of the pre-merger SMBH binary. Such a recoiling SMBH may be detectable as an active galactic nucleus (AGN) broad-line region offset by up to 10 kpc from a disturbed host galaxy. We describe a novel methodology using forward modeling with The Tractor to search for such offset AGNs in a sample of 5493 optically variable AGNs detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 124 publications
1
22
0
Order By: Relevance
“…Lacking an outward-pointing, comet-like appearance, we suspect that this active 15 star cluster is probably not an ejected nucleus from a gravitational wave recoil event (Blecha & Loeb 2008;Holley-Bockelmann et al 2008;Komossa & Merritt 2008;Askar et al 2021;Hogg et al 2021;Ward et al 2021). Although probably evident to many readers, we note that Nikhuli has a lopsided shape, unlike that of a (background) galaxy.…”
Section: Infall Timescalementioning
confidence: 79%
“…Lacking an outward-pointing, comet-like appearance, we suspect that this active 15 star cluster is probably not an ejected nucleus from a gravitational wave recoil event (Blecha & Loeb 2008;Holley-Bockelmann et al 2008;Komossa & Merritt 2008;Askar et al 2021;Hogg et al 2021;Ward et al 2021). Although probably evident to many readers, we note that Nikhuli has a lopsided shape, unlike that of a (background) galaxy.…”
Section: Infall Timescalementioning
confidence: 79%
“…It may also be that the use of the qsofit modeling technique based on the goodness of fit of a DPW to the light curve (Butler & Bloom 2011) used by (Baldassare et al 2020b) can allow for some supernova contamination. In Ward et al (2021) we found that qsofit could produce good DRW fits to supernovae light curves in ZTF and the σ QSO statistic needed comparison to a goodness of fit statistic from an SN model in order to separate SN and AGN populations.…”
Section: Discussionmentioning
confidence: 94%
“…Future work on these candidates will include forward modeling of ZTF and DECam images to fit for their positions relative to their host galaxies and determine the fraction which are wandering about their galaxy halo. The potential for forward modeling of ZTF images to determine the position of a variable point source relative to its host galaxy was demonstrated in Ward et al (2021) for recoiling SMBH candidates and will provide a way to confirm the positions of IMBH candidates without X-ray or radio detections. These candidates are just the tip of the iceberg in the search for optically variable AGN in dwarf galaxies, which will be greatly enhanced by the capabilities of the Legacy Survey of Space and Time (LSST) at Vera C. Rubin Observatory (Ivezić et al 2019) over the next decade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations